2x+5y=-13
3x-4y=-8
Rearrange the first equation to solve for x in terms of y. This will be needed to apply the substition method.
2x+5y=-13
2x=-5y-13
x=-5/2y-13/2
Now plug this in for x in the second equation.
3(-5/2y-13/2)-4y=-8
-15/2y-39/2-4y=-8
-23/2y-39/2=-8
-23/2y=11.5
y=-1
Now plug this y value in to one of the original equations.
2x+5(-1)=-13
2x-5=-13
2x=-8
x=-4
Final answer: (-4,-1). <=============
To check:
2(-4)+5(-1)=-13
-8+5(-1)=-13
-8-5=-13
-13=-13
True
3(-4)-4(-1)=-8
-12-4(-1)=-8
-12+4=-8
-8=-8
True